Shifting Parental Age Differences in High-Income Countries: Insights and Implications - Christian Dudel; Yen-hsin Alice Cheng; Sebastian Klüsener (Population and Development Review, 2023)
Age differences within couples are of considerable importance for the power relations between partners. These age differences become particularly relevant when couples transition to having a(nother) child, as such an event often results in a renegotiation of the gendered division of labor. Surprisingly, the literature on female empowerment and fertility postponement has so far paid little attention to parental age differences. This paper makes use of a new data set to present a demographic analysis of trends in parental age differences at childbirth in 15 high-income countries, covering a period in which all of these countries experienced changes in gender relations and fertility postponement. The general trends in rising mean ages at childbirth have evolved quite similarly among men and women. However, we demonstrate that these similarities hide previously unexplored and highly gendered disparities in parental age differences. Older mothers report much smaller mean parental age differences than younger mothers, and this age pattern among mothers has further polarized over time. By contrast, older fathers report larger parental age differences than younger fathers, while the disparities by age among fathers have not changed much over time. We discuss the relevance of our findings at both the individual and the societal level.
Keywords: 300